Risk Factors of In-Hospital Mortality of Ischemic Stroke Patients in Gunung Jati General Hospital - Andini, El Alsha; Dewangga, Raditya; Adrialmi (HM Publisher, 2024)
Background: Stroke is the leading cause of death and the most significant contributor to disabilities worldwide. Predicting the mortality of stroke patients and giving optimal care remain challenges in developing countries like Indonesia. In this study, we aimed to identify factors associated with in-hospital mortality after acute ischemic stroke. Methods: The study conducted a retrospective cohort of cerebral infarct patients administered in 2022 to Gunung Jati General Hospital, West Java, Indonesia. This study included hospitalized patients with a clinical history of stroke confirmed by a CT scan or MRI. The clinical data, radiology, and laboratory tests were collected at admission or within 24 hours after admission. Results: This study involved a total of 92 ischemic stroke patients with a median age of 62. The most prevalent comorbidities were dyslipidemia (93.5%), hypertension (83.7% of patients), and concomitant infection (50%). Patients who experienced in-hospital mortality had a significantly higher number of comorbidities, such as chronic kidney disease, concomitant infection, and atrial fibrillation. Statistically higher neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio were also shown in non-survived patients. Ischemic stroke patients with concomitant infection and atrial fibrillation, respectively, had 6.679 (aOR: 6.679, 95% CI 1.802-27.029) and 6.904 times (aOR: 6.904, 95% CI 1.290-36.959) greater to have in-hospital mortality. Conclusion: Concomitant infection and atrial fibrillation were associated with in-hospital mortality in ischemic stroke patients at Gunung Jati General Hospital. The findings indicated the importance of identifying timely management for improving better outcomes.